High atmospheric carbon dioxide-dependent alleviation of salt stress is linked to RESPIRATORY BURST OXIDASE 1 (RBOH1)-dependent H(2)O(2) production in tomato (Solanum lycopersicum) - Yi, Changyu (J Exp Bot, 2015)
Plants acclimate rapidly to stressful environmental conditions. Increasing atmospheric CO(2) levels are predicted to influence tolerance to stresses such as soil salinity but the mechanisms are poorly understood. To resolve this issue, tomato (Solanum lycopersicum) plants were grown under ambient (380 μmol mol(–1)) or high (760 μmol mol(–1)) CO(2) in the absence or presence of sodium chloride (100mM). The higher atmospheric CO(2) level induced the expression of RESPIRATORY BURST OXIDASE 1 (SlRBOH1) and enhanced H(2)O(2) accumulation in the vascular cells of roots, stems, leaf petioles, and the leaf apoplast. Plants grown with higher CO(2) levels showed improved salt tolerance, together with decreased leaf transpiration rates and lower sodium concentrations in the xylem sap, vascular tissues, and leaves. Silencing SlRBOH1 abolished high CO(2) -induced salt tolerance and increased leaf transpiration rates, as well as enhancing Na(+) accumulation in the plants. The higher atmospheric CO(2) level increased the abundance of a subset of transcripts involved in Na(+) homeostasis in the controls but not in the SlRBOH1-silenced plants. It is concluded that high atmospheric CO(2) concentrations increase salt stress tolerance in an apoplastic H(2)O(2) dependent manner, by suppressing transpiration and hence Na(+) delivery from the roots to the shoots, leading to decreased leaf Na(+) accumulation.